Dispersão urbana e legislação urbanística na formação do território de Colatina - Barroca, Denise Aparecida de Souza (2023)
This dissertation, developed in the Graduate Program in Architecture and Urbanism at the Federal University of Espírito Santo, has the general objective of verifying the presence of characteristics of urban dispersion in the formation of the territory of Colatina (Espírito Santo, Brazil), mainly from the subdivisions approved by the City Hall. For this, the methodological strategy adopted was based on the specialized theoretical framework and sought to identify characteristics, here referred to as variables, intrinsic to this contemporary urbanization: a) the growth of the urban population and territory, with a predominance of the second over the first; b) alternation between areas with high and low densities in the center-periphery direction, and; c) territorial discontinuity with formation of urban voids. In order to develop these analyses, it was necessary, in addition to knowing the concepts of urban dispersion, to understand how regular urban territory is formed through urban legislation. At the same time it was essential to know the data and the urban form of the city, confronting the growth of the regular fabric and its particularities with the trends of urban dispersion. As a time frame, the period between 1979 and 2022 was defined, addressing the expansion of that territory since the delimitation of its first urban perimeter. In the end, it was concluded that Colatina presents characteristics of urban dispersion, as well as urban fragments in territorial discontinuity located on the edges of the main fabric. The identified clippings are commonly of a residential and/or industrial nature, with the presence of subdivisions approved by the municipal government. In short, the following chapters structured this dissertation: theoretical and conceptual bases, presentation and characterization of the territorial area, methodological procedures, analysis of the research object and final considerations.